A period of rapid development for equestrianism in China: from 2015 to 2020 - Jiaxin, L.; López Adán, E.; de la rubia, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction: Chinas domestic horses established the foundations for commerce, communication, and state infrastructure along the old Silk Road in China [1] As trade patterns changed, the use of horses changed from trade to a sport and recreation. Chinas modern equestrian business has developed significantly over the previous decades, and the expansion between 2015 and 2020 is essential, as China implements further policies to aid in the development of modern equestrianism. The equestrian sport can propel the horse industry forward, and the horse industry is a unique business in that it integrates primary, secondary and tertiary sectors, with plenty of space for growth. With the "dual circulation" strategy published, the service sector is largely non-tradable. [2] A countrys economic development and national income are positively correlated with its service sector. [3] Sports play a large role within this sector. Equestrian sports also positive changed with the general environment of sports development. This study assesses the development of equestrianism in China from four perspectives: the general sports economic environment; the development of equestrian activities; the economic industries driven by equestrian activities; and relevant equestrian policies. Problems in the current development of equestrian sports are pointed out and recommendations are made.